Prognostic nutritional index is related to myocardial performance index in newly diagnosed nondiabetic hypertensive patients - Ahmet Seyda Yılmaz; Elif Ergül; Ömer Faruk Çırakoğlu; Nadir Emlek; Mustafa Çetin (Clinical and Experimental Hypertension, 2021)
Background: Arterial hypertension (AH) leads to systolic and/or diastolic dysfunction of the left ventricle (LV) by causing structural changes in the myocardium. Myocardial performance index (MPI) provides the evaluation of LV systolic and diastolic functions together. Prognostic nutritional index (PNI) is an indicator of immunonutritional status. PNI was studied in patients with malignancy, malnutrition, and cardiovascular diseases so far. It was aimed to investigate the relationship between PNI and MPI in hypertensive patients. Methods: A total of 91 consecutive patients with newly diagnosed AH were included in the study. PNI was calculated according to the following formula: ((10 × serum albumin (g/dL))+(0.005 × total lymphocyte count)). MPI was obtained by dividing the sum of isovolumetric relaxation time (IVRT) and isovolumetric contraction time (IVCT) by the ejection time (ET) ((IVRT+IVCT)/ET). Patients were divided into two groups according to MPI is above or below the value of 0.5. The demographic characteristics and PNI values of patients were compared between two groups. Results: There were 65 patients in the higher and 26 patients were in the normal MPI group. Higher MPI group had male predominance (p = .002). Diastolic blood pressure (p = .021), interventricular septum thickness (p = .005), posterior wall thickness (PWT) (p = .001), serum albumin concentration (p = .045), and PNI (p = .013) were differed between groups. Multivariate logistic regression analysis revealed that PWT [OR = 1.835, 95% CI: 1.126–2.992, p = .015] and PNI [OR = 1.161, 95% CI: 1.004–1.343, p = .018] predicted higher MPI. Conclusion: Higher PNI was an independent predictor of LV dysfunction in newly diagnosed hypertensive patients. Immunonutritional status may be used as an indicator of the left ventricular function in patients with AH.